From city centre to urban edge: habitat heterogeneity and environmental filtering determine breeding bird community structure in an expanding Mediterranean city - Luis M. Carrascal; Xabier Esparza; Juan Arizaga (Urban Ecosystems, 2026)
Urban expansion alters animal communities through habitat fragmentation, environmental filtering and functional homogenisation. Understanding how urban habitats shape species assemblages is essential for urban planning that balances development with biodiversity conservation. We analysed the breeding bird community in Pamplona, northern Spain, a Mediterranean city that has experienced 40% population growth over the last five decades, examining how assemblages responded to habitat structure across the centre-periphery gradient. We detected 66 species organised according to the species-sorting paradigm, with two main Mediterranean assemblages: urban core specialists ( Passer domesticus , Columba livia , Motacilla alba , Delichon urbicum ) and peripheral species linked to natural habitats ( Sylvia atricapilla , Troglodytes troglodytes , Luscinia megarhynchos , Hippolais polyglotta ). Water cover had the strongest positive effect on richness (+ 3.2 species per 10% habitat coverage), followed by gardens (+ 1.6 species per 10%), while building and street cover reduced richness (-1.0 to -1.5 species per 10%). Centre-periphery differences in species richness were measurable only at scales greater than 50 hectares, with 60 species in 120 ha in the urban periphery versus 40 in the centre, reflecting pronounced habitat filtering favouring birds with preferences for wooded habitats and wetlands. Water bodies and well-wooded green areas functioned as biodiversity hotspots. The city’s outskirts contributed to gamma diversity with rare species, highlighting the need for ecotonic and permeable urban boundaries, which should be established by landscape conservation strategies in expanding Mediterranean cities.

Wastewater reduction of Salmonella Typhimurium and H2S by using TiO2 films deposited by spin coating or magnetron sputtering - Luz A. Rincón-Barón; Luis A. Cañón-Tafur; María P. Forero-Carvajal; Laura G. Ramírez-Alemán; Luis C. Jiménez-Borrego; Lucia A. Díaz-Ariza; Augusto E. Mejía-Gómez; Camilo Velez; Ana K. Carrascal-Camacho; Claudia M. Rivera-Hoyos; Aura M. Pedroza-Rodríguez (International Journal of Hygiene and Environmental Health, 2026)

Beyond coverage: Effectiveness of Natura 2000 network in conserving breeding bird populations in a highly anthropogenic region - Juan Arizaga; Maite Laso; Olatz Aizpurua; Luis M. Carrascal (Journal for Nature Conservation, 2026)

Limited winter constraints in a recent translocated endangered island bird - Luis M. Carrascal; Alejandro Delgado; Víctor Suárez (Journal for Nature Conservation, 2026)

Alarming conservation status of Western European steppe birds and their habitats: An expert-based review of current threats, traits and knowledge gaps - Julia Gómez-Catasús; Ana Benítez-López; Mario Díaz; David González del Portillo; Cristian Pérez-Granados; Juan Carlos Alonso; Beatriz Arroyo; Inmaculada Abril-Colón; Adrián Barrero; Rafael Barrientos; Luis Bolonio; Gerard Bota; et al. (Biological Conservation, 2025)

Pilot plant use of two types of TiO2 thin-films as a sustainable alternative for reuse of kitchen greywater - Luz A. Rincón-Barón; Luis A. Cañón-Tafur; Catalina Gómez-Prias; Mayra A. Garzón-González; Camila Gracia-Sánchez; Camilo Quiñonez-Casallas; Luis C. Jiménez-Borrego; Lucia A. Díaz-Ariza; Augusto E. Mejía-Gómez; Camilo Velez; Ana K. Carrascal-Camacho; Claudia M. Rivera-Hoyos; et al. (Journal of Water Process Engineering, 2025)

Establishment success of the reinforced population of Gran Canaria Blue Chaffinch Fringilla polatzeki - Alejandro Delgado; Víctor Suárez; Daniel González; Domingo Trujillo; Luis M. Carrascal (Journal of Ornithology, 2024)
The Gran Canaria Blue Chaffinch is the rarest forest passerine in the western Palaearctic with a population reduced to a single locality, Inagua, in the west of the island. After a forest fire, some birds were established in another location and a reinforcement programme was launched with the aim of consolidating this new population. Between 2010 and 2019, 194 Blue Chaffinches were released in the pine forest of La Cumbre, in the centre of the island and at a higher altitude than the previous one. Birds of two origins were used for this action: captive-bred birds were released using “soft” release methods, and wild-caught birds from the Inagua source population were released using “hard” release methods. Survival of radio-tagged birds (20–42 days of battery life) was high and similar between the two groups. Wild-caught birds occupied 12–15 times more surface area than captive-bred birds that remained close to supplementary feeding sites. All translocated birds displayed breeding behaviour in the following breeding season, although the rate of contribution to the new population was significantly lower for wild-caught birds (21% compared to 54% for captive-bred birds). This disparity can be partly attributed to nearly one-fifth of the wild-caught birds returning to Inagua. We conclude that the establishment phase of the Blue Chaffinch reinforced program in Gran Canaria has been successful. To retain wild-caught birds and deter their return to the source population, we recommend employing methods akin to the soft-release techniques utilized for captive-bred birds. Ongoing monitoring of the enhanced population, collecting data on survival and breeding success, will enable the evaluation of the long-term success of the translocation program.

Impact of climate and land degradation on soil carbon fluxes in dry semiarid grasslands in SE Spain - Ana Rey; Luis M. Carrascal; Carlos García-Gutiérrez Báez; João Raimundo; Cecilio Oyonarte; Emiliano Pegoraro (Plant and Soil, 2021)

Macro‐spatial structure of biotic interactions in the distribution of a raptor species - Pedro Aragón; Luis M. Carrascal; David Palomino (Journal of Biogeography, 2018)
Aim While the contribution of abiotic factors to species distribution is well known, the geographic structure, if any, of biotic interactions within the species range is poorly understood. Most studies neglect biotic interactions when generating Species Distribution Models (SDMs) and projecting them, using future climatic scenarios, while others argue that biotic interactions may extend species tolerances to suboptimal abiotic conditions. Elucidating the extent to which biotic interactions play a role at a macro‐scale is challenging due to its inherent complexity. In this study, we characterized the independent contribution of prey abundance distributions on the Merlin's wintering distribution ( Falco columbarius ). Then, to examine the hypothesis that biotic interactions may counteract other suboptimal conditions, we tested for a differential importance of physical habitat characteristics and prey abundance distributions along the species’ wintering range. Location Peninsular Spain. Methods We modelled the Merlin's geographic distribution with Boosted Classification Trees as a function of environmental predictors (environmental model) and prey relative abundances (prey model), either separately or jointly (combined model). We tested whether the predictive success of environmental and prey models differ spatially. Results Partialling out the variation into independent components we found that the prey abundance distributions explained the largest part of variation. Furthermore, the first four predictors with the highest contribution in our combined models were the abundances of prey species. Finally, our model predictions revealed a north‐to‐south increase in the importance of prey abundance distributions. Interestingly, our results suggest that biotic interactions can enable species to inhabit a wider range of suboptimal habitat conditions on range margins. Main conclusions Relevant biotic interactions may not be always fully interchangeable with environmental surrogates. Abiotic factors and biotic interactions may shape species range limits and cores of distributions differently. Neglecting biotic interactions may compromise spatiotemporal transferability of SDMs, especially on species margins, and hence their applicability.

Wintering forest birds roost in areas of higher sun radiation - Sara Villén-Pérez; Luis M. Carrascal; Oscar Gordo (European Journal of Wildlife Research, 2014)

Species abundance and migratory status affects large-scale fruit tracking in thrushes (Turdus spp.) - José L. Tellería; Luis M. Carrascal; Tomás Santos (Journal of Ornithology, 2014)

Explanations for bird species range size: ecological correlates and phylogenetic effects in the Canary Islands - Luis M. Carrascal; Javier Seoane; David Palomino; Vicente Polo (Journal of Biogeography, 2008)
Aim To explore the determinants of island occupancy of 48 terrestrial bird species in an oceanic archipelago, accounting for ecological components while controlling for phylogenetic effects. Location The seven main islands of the Canary archipelago. Methods We obtained field data on population density, habitat breadth and landscape distribution in Tenerife, Fuerteventura and La Palma, aiming to sample all available habitats and the gradient of altitudes. In total, 1715 line transects of 0.5 km were carried out during the breeding season. We also reviewed the literature for data on occupancy, the distance between the Canary Islands and the nearest distribution border on the mainland, body size and endemicity of the 48 terrestrial bird species studied. Phylogenetic eigenvector regression was used to quantify (and to control for) the amount of phylogenetic signal. Results The two measurements of occupancy (number of occupied islands or 10 × 10 km UTM squares) were tightly correlated and produced very similar results. The occupancy of the terrestrial birds of the Canary Islands during the breeding season had a very low phylogenetic effect. Species with broader habitat breadth, stronger preferences for urban environments, smaller body size, and a lower degree of endemicity had a broader geographical distribution in the archipelago, occupying a larger number of islands and 10 × 10 UTM squares. Main conclusions The habitat‐generalist species with a tolerance for novel urban environments tend to be present on more islands and to occupy a greater area, whereas large‐sized species that are genetically differentiated within the islands are less widespread. Therefore, some properties of the ranges of these species are explicable from basic biological features. A positive relationship of range size with local abundance, previously shown in continental studies, was not found, probably because it relies on free dispersal on continuous landmasses, which may not be applicable on oceanic islands.

Interspecific differences in population trends of Spanish birds are related to habitat and climatic preferences - Javier Seoane; Luis M. Carrascal (Global Ecology and Biogeography, 2008)
Aim Animal monitoring programmes have allowed analyses of population trends, most of which now comment on the possible effect of global climate change. However, the relationship between the interspecific variation in population trends and species traits, such as habitat preferences, niche breadth or distribution patterns, has received little attention, in spite of its usefulness in the construction of ecological generalizations. The objectives of this study were: (1) to determine whether there are characteristics shared among species with upwards or downwards trends, and (2) to assess whether population changes agree with what could be expected under global warming (a decrease in species typical of cooler environments). Location The Spanish part of the Iberian Peninsula ( c. 500,000 km 2 ) in the south‐western part of the Mediterranean Basin. Methods We modelled recent breeding population changes (1996–2004), in areas without apparent land use changes, for 57 common passerine birds with species‐specific ecological and distributional patterns as explanatory variables. Results One‐half of these species have shown a generalized pattern towards the increase of their populations, while only one‐tenth showed a significant decrease. One half (54%) of the interspecific variability in yearly population trends is explained considering species‐specific traits. Species showing more marked increases preferred wooded habitats, were habitat generalists and occupied warmer and wetter areas, while moderate decreases were found for open country habitats in drier areas. Main conclusions The coherent pattern in population trends we found disagrees with the proposed detrimental effect of global warming on bird populations of western Europe, which is expected to be more intense in bird species inhabiting cooler areas and habitats. Such a pattern suggests that factors other than the increase in temperature may be brought to discussions on global change as relevant components to explain recent changes in biodiversity.